A Household-based analysis of domestic energy consumption for lighting in Jaipur City (International Journal of Built Environment and Sustainability, 2016)
India being the third largest economy of the world, more than two third of the total population lives in villages and started to consuming more quantity of energy in the recent years. Though the electricity consumption in the domestic sector has increased up to 22 per cent of the total electricity consumption, electricity consumption in villages is very less, since good number of villages in the rural system are not even electrified. In urban areas almost 90 percent of the household use electricity for lighting and just 10 percent use kerosene for the said purpose, whereas in the rural areas still more number of households use kerosene for lighting purposes. In this paper an attempt is made to analyze the domestic energy consumption for lighting in Jaipur city. Good amount of literature collected pertaining to domestic energy consumption for lighting purposes across the globe, analyzed thoroughly and presented. Further, a household survey was conducted among 684 households in Jaipur city by employing pre-tested schedule. The schedule has few variables including identification particulars, economic conditions, demographic pattern, domestic lighting appliances at the household level; and the energy consumption pattern. Further the collected data are analyzed and a multiple regression model was developed by considering the total electricity consumption as dependent variable ‘Y’ and the electrical appliances for lighting purposes, such as the number of incandescent bulbs, tube lights, CFL, and LED are considered as ‘X’ variables; and this study conclude with plausible findings and recommendations.